2013
DOI: 10.1002/ijc.28320
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor activity mediated by human 4‐1BB‐engineered T cells

Abstract: 4-1BB (CD137) is a costimulatory molecule transiently expressed on the T-cell surface after TCR engagement, whereas its ligand 4-1BBL can be found on professional antigen-presenting cells, but more importantly, also on tumor cells. As the role of the 4-1BB/4-1BBL pathway has emerged central to CD81 T-cell responses and survival, we sought to test its relevance in the context of genetically modified human T cells. To that end, T cells purified from healthy donors and from vaccinatedmelanoma patients were transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…1) [217] by T cells can promote cell proliferation both in vitro and in vivo. Moreover, we recently showed that the constitutive expression of 4-1BB/CD137 in engineered T cells can lead to improved cytokine secretion, proliferation and cytotoxicity in vitro an in ovo model we developed [218].…”
Section: Use Of Chimeric Co-stimulation And/or Switch Receptorsmentioning
confidence: 97%
“…1) [217] by T cells can promote cell proliferation both in vitro and in vivo. Moreover, we recently showed that the constitutive expression of 4-1BB/CD137 in engineered T cells can lead to improved cytokine secretion, proliferation and cytotoxicity in vitro an in ovo model we developed [218].…”
Section: Use Of Chimeric Co-stimulation And/or Switch Receptorsmentioning
confidence: 97%
“…31 We further showed that such an approach may be enhanced at the protein level (TCR structure), [32][33][34][35] or by improving cellular function. 36,37 However, further advancement of T-cell based therapy requires methods that can overcome the challenges of clinical treatment. We propose a novel, clinically applicable methodology for non-invasive longitudinal and quantitative tumor-specific T-cell tracking, based on the combination of CT as an imaging modality and gold nanoparticles (GNPs) as labeling agents.…”
mentioning
confidence: 99%
“…[5,6] An alternative approach uses genetically modified human T-cells to express higher TNFRSF9 levels. [7] TNFRSF9 stimulation has been suggested as a treatment for metastatic cancers. [8] However, to date there is only poor data about the distribution of TNFRSF9 in brain metastases, which still constitute one of the most deleterious clinical conditions in tumor patients.…”
Section: Introductionmentioning
confidence: 99%